2015
DOI: 10.1371/journal.pone.0141958
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Acceptable Level of Risk: Incorporating the Economic Cost of Under-Managing Invasive Species

Abstract: Management of nonindigenous species includes prevention, early detection and rapid response and control. Early detection and rapid response depend on prioritizing and monitoring sites at risk for arrival or secondary spread of nonindigenous species. Such monitoring efforts require sufficient biosecurity budgets to be effective and meet management or policy directives for reduced risk of introduction. Such consideration of risk reduction is rarely considered, however. Here, we review the concepts of acceptable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…Continuous improvement and application of pathway and habitat modeling are likely to bring greater societal benefits. Finally, as reviewed above and emphasized by other recent theoretical and empirical studies (23,168,208), ecological and bioeconomic analyses have demonstrated that greater investments in prevention and other management activities early in the invasion process almost always bring net benefits. Increased cross disciplinary training in ecology and economics to increase research capacity in bioeconomics, and coproduction of research with decision makers (209), would enable more widespread management improvements.…”
Section: Discussionmentioning
confidence: 80%
“…Continuous improvement and application of pathway and habitat modeling are likely to bring greater societal benefits. Finally, as reviewed above and emphasized by other recent theoretical and empirical studies (23,168,208), ecological and bioeconomic analyses have demonstrated that greater investments in prevention and other management activities early in the invasion process almost always bring net benefits. Increased cross disciplinary training in ecology and economics to increase research capacity in bioeconomics, and coproduction of research with decision makers (209), would enable more widespread management improvements.…”
Section: Discussionmentioning
confidence: 80%
“…A respondent that believes that they are aware of NIMS, but cannot recognise them, creates a false sense of a biosecure plebiscite and in turn results in overconfidence in managers (personal observations). If management assumes a precautionary approach (e.g., [ 38 – 40 ]) then inaccurate knowledge represents a hazard that needs to be managed.…”
Section: Discussionmentioning
confidence: 99%
“…Knowledge acquired from past invasions to determine high(er) probability locations and timing of new invasions; and 3. Having the tools, methods, resources (expertise and funding), governance and communication networks in place to ensure the surveillance objectives can be met (e.g., Davidson et al 2015).…”
Section: Surveillance and Detectionmentioning
confidence: 99%
“…An epidemiological approach that utilises network theory (e.g., Kiss et al 2006;Youssef et al 2011) to create hub and spoke models (e.g., Azmi et al 2015) could be useful for identifying the starting point of an outbreak and the subsequent spread both temporally and spatially. The surveillance regime would need to be sensitive enough to detect the pests at an appropriate scale while also at low enough densities, but requires understanding of trade-offs between effort and benefit (e.g., Davidson et al 2015). Passive surveillance (Campbell et al 2007) might be a useful tool to detect unwanted species and has been used in Darwin, Australia, to detect the black striped mussel (Willan et al 2000).…”
Section: Surveillance and Detectionmentioning
confidence: 99%